2008
DOI: 10.1177/1363461508094674
|View full text |Cite
|
Sign up to set email alerts
|

Health Seeking for Ambiguous Symptoms in Two Cultural Groups: A Comparative Study

Abstract: This study examined cultural differences in health seeking for medically ambiguous symptoms in women from two culturally diverse communities. Thirty-five South Asian immigrants and 36 European Americans participated in a health history interview. Though the types and relative frequencies of practices were similar across the two groups, the goals and underlying logic supporting practices differed sharply. Among European Americans, practices were focused on the need to increase energy, creativity, and output; am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
13
0
3
Order By: Relevance
“…Like participants in Katz's study, the HMC informants were all pensioners and their somewhat advanced age perhaps increased their focus on maintaining their good health and preventing illness. However, studies with younger participants have reported similar findings; the conceptual models of cause and cure are rooted in the body as an individual project in some populations (Karasz and Dempsey 2008). For some populations, therefore, reducing potential health risks is an imperative, wherein "numerical results of check-ups and home monitoring are appreciated and became central in individual processes of taking control over and responsibility for one´s health" (Andersen and Whyte 2014:266).…”
Section: Consuming Healthmentioning
confidence: 93%
See 1 more Smart Citation
“…Like participants in Katz's study, the HMC informants were all pensioners and their somewhat advanced age perhaps increased their focus on maintaining their good health and preventing illness. However, studies with younger participants have reported similar findings; the conceptual models of cause and cure are rooted in the body as an individual project in some populations (Karasz and Dempsey 2008). For some populations, therefore, reducing potential health risks is an imperative, wherein "numerical results of check-ups and home monitoring are appreciated and became central in individual processes of taking control over and responsibility for one´s health" (Andersen and Whyte 2014:266).…”
Section: Consuming Healthmentioning
confidence: 93%
“…However, Lupton (1997:379-80) points out how a focus on consumerism may ignore a number of complex aspects of health care seeking, such as the embodied and affective dimensions of illness and the unequal power relation intrinsic to the clinical encounter. More recent studies focusing on social groups and the management of health care in less 8 affluent settings demonstrate considerable social differences in modes of appropriation, including the moral discourses underlying health practices and beliefs in different social and cultural classes (Garro 2011, Karasz andDempsey 2008). These works illustrate the intrinsic tie between health and wellbeing and the concerns and demands of the enactment of everyday life.…”
Section: The Patient As a Consumermentioning
confidence: 99%
“…Las creencias de la población general sobre la salud y la enfermedad han sido un tema de interés para el campo de las investigaciones en salud, dado que las representaciones sociales 17 sobre la aflicción y la cura impactan sobre la manera enque las personas se comportan ante experiencias de enfermedad [18][19][20][21] . Teniendo en cuenta que los diarios y revistas de difusión masiva son una fuente importante de información consultada por el público en general -y que pueden influir en los preconceptos de la población sobre los temas de salud 22 , consideramos esencial indagar sobre estas cuestiones para registrar las creencias de las personas en relación a temas de salud.…”
Section: Introductionunclassified
“…Teniendo en cuenta que los diarios y revistas de difusión masiva son una fuente importante de información consultada por el público en general -y que pueden influir en los preconceptos de la población sobre los temas de salud 22 , consideramos esencial indagar sobre estas cuestiones para registrar las creencias de las personas en relación a temas de salud. El caso de la FM es en particular interesante -como también el autismo 23 o la sexualidad 24 -dado el carácter controvertido del diagnóstico, que podría caracterizarse como un cuadro "ambiguo" 19 , que se presentan más permeables a los efectos de la cultura y el contexto.…”
Section: Introductionunclassified
“…Los motivos de selección de las terapias no convencionales han sido atribuidos a diversos factores, entre los que se destacan la insatisfacción con el modelo biomédico de atención de la salud-enfermedad (Boon, Brown, Gavin, Kennard, & Stewart, 1999), la demanda de un nuevo tipo de relación con el especialista terapéutico y a los límites del paternalismo biomédico (Montgomery, 2006), la aparición de nuevas subjetividades que, en el contexto de la posmodernidad, asignan un rol central de responsabilidad al sujeto en el cuidado de su salud (Siahpush, 1998), la búsqueda de nuevos estilos de terapia más suaves, holísticos y menos invasivos que la biomedicina alopática (Douglas, 1998;Vincent & Furnhman, 1996), el surgimiento de movimientos sociales asociados a la Nueva Era (Albanese, 1990;Carozzi, 2001;Shimazono, 1999), entre otros. Ha sido señalado también el importante rol que, desde la perspectiva de los usuarios, cumplen estas medicinas frente al tratamiento de enfermedades graves o crónicas, tales como el caso del cáncer (Broom & Tovey, 2008), el asma (Freidin & Timmermans, 2008), cardiopatías (Ai & Bolling, 2002), sintomatología "ambigua" (Karasz & Dempsey, 2008), hasta distintos trastornos mentales, como depresión (Berenzon Gorn, Navarro, & Saavedra Solano, 2009) y trastornos de ansiedad (Eisenberg et al, 1998). De hecho, de acuerdo a varios estudios internacionales, la mayoría de los pacientes con trastornos mentales acuden a una utilización mayor de tratamientos alternativos (p.e.…”
unclassified